Peranan Faktor Promosi Dalam Memasarkan Produk Terhadap Perilaku Pembelian Online Di Masa Pandemi Covid-19 (Studi Kota Tanjungpinang) - Iranita Iranita (Bahtera Inovasi, 2020)
The COVID-19 pandemic followed by the implementation of social distancing gave rise to new consumer behavior, but on the one hand it turned out to open opportunities for banking, financial, and financial services businesses to spur marketing. One of the results of the analysis is that the pandemic situation apparently gave rise to new consumer behavior. Businesses optimize online marketing and digital branding as a means of communication with their target customers. Supported by the rapid growth of information technology has created new business opportunities in pursuit of business success. The purpose of this study is to find out the role of promotional factors towards online purchasing behavior during COVID-19. This research is explanatory research using factor analysis. In this study, the number of variables set was 7 variables related to factors related to the behavior of online purchases during the COVID-19 pandemic. The results of this study are promotional factors, is the only strong factor in influencing the behavior of online purchases during COVID-19 in Tanjungpinang, where the growth of technology developments especially in the COVID-19 period has driven webonline sparking enthusiasm to develop responsive customer promotions